IDENTITY CRISIS IN THE DIGITAL AGE AND THE DEPENDENCE OF SOCIAL MEDIA - Xalilova Tabassum Akmaljon daughter (TADQIQOTLAR, 2025)
ANNOTATION This article analyzes the psychological consequences of the digital age, in particular, the factors that lead to the identity crisis of social networks. Virtuality on digital platforms, the creation of artificial images, constant comparison syndrome, and the occasional FOMO syndrome (fear of missing out) threaten the mental stability of modern people.